O comércio mundial de produtos químicos e o acordo de harmonização de tarifas - Covolo, Marcela Carolina Siqueira (2008)
Can a bound tariffs harmonization agreement for a specific sector increase the trade flow among countries? Does it diminish industries competitiveness in some countries? The aim of this assignment is to analyze chemicals international trade flow after Chemical Tariff Harmonization Agreement has taken place. In this sense, the Balassa Index methodology was chosen to define the revealed comparative advantage among countries. As a result, the access to lower cost capital and raw material has defined the chemical industry competitiveness. The tariff reduction by CTHA has not changed the competitiveness among countries but has improved sector exports by the inclusion of underdeveloped countries into chemicals trade flow